Secondary battery and electric device

By using a mixed cathode material of low specific surface area lithium iron phosphate chemical system materials and ternary chemical system materials in lithium-ion batteries, the agglomeration problem is solved, compatibility and processing performance are improved, and the performance of lithium-ion batteries is improved and stable.

CN119864401APending Publication Date: 2025-04-22CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510080260.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2020-09-30
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

How to achieve performance improvement and stability in lithium-ion batteries, ensure electrical performance and ensure good processing performance in the preparation process.

Method used

By screening and reasonably matching the types and micromorphology of different types of materials, a mixed cathode material, including lithium iron phosphate chemical system materials and ternary chemical system materials with low specific surface area, avoiding agglomeration problems and improving compatibility and processing performance.

Benefits of technology

The compatibility and processing performance of hybrid cathode materials are improved, the cycle life of lithium-ion batteries is extended, and the electrochemical performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864401A_ABST
    Figure CN119864401A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and a power utilization device, a mixed positive electrode material of the secondary battery comprises a mixed component of a lithium iron phosphate chemical system material and a ternary chemical system material, and the lithium iron phosphate chemical system material is secondary particles with a specific surface area average value of 3-10m < 2 > / g. According to the mixed positive electrode material disclosed by the invention, secondary particle lithium iron phosphate with low specific surface area is introduced, so that the processing performance of the mixed positive electrode material is improved, the slurry is not easy to agglomerate, and the two materials are well compatible. When the mixed positive electrode material is used for preparing the positive electrode plate, the distribution uniformity of the positive electrode material on the positive electrode plate can be effectively improved, and the distribution uniformity of the resistance of the electrode plate can be adjusted, so that the electrochemical performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application based on the invention with application number 2020800971803, application date September 30, 2020, and invention name “Mixed positive electrode material, positive electrode sheet and preparation method, battery and electrical device”. Technical Field

[0002] The present application belongs to the technical field of lithium-ion batteries, and specifically relates to a secondary battery and an electrical device. Background Art

[0003] Lithium-ion batteries are highly competitive in the field of secondary batteries because of their high energy density, long cycle life, no memory effect, and green environmental protection. They are not only widely used in terminal electronic products such as mobile phones and laptops, but also gradually increase their applications in electric vehicles, large-scale energy storage equipment, and other fields. As the positive electrode material of lithium-ion batteries, the more mature and widely used ones are mainly lithium iron phosphate material systems (such as lithium iron phosphate or doped modified lithium iron phosphate materials) and ternary material systems (such as nickel cobalt manganese oxide and nickel cobalt aluminum oxide system materials). Lithium-ion batteries with ternary system materials as positive electrode active materials have attracted attention in the industry during a certain period of development because of their higher energy density and better power performance, and have become a research direction. However, the two types of materials have their own strengths and weaknesses. With the deepening of cognition and research, how to use their respective advantages has also begun to attract attention.

[0004] However, how to achieve performance improvement and stabilization of lithium-ion batteries, ensure the electrical performance of lithium-ion batteries, and at the same time ensure good processing performance during the preparation process has become one of the technical problems that need to be solved urgently. Summary of the invention

[0005] The present application provides a mixed positive electrode material, which solves the problem of easy agglomeration of different types of materials when mixed by screening and reasonably matching the types and micromorphologies of the materials used, so that the compatibility and processing performance of the mixed positive electrode material are better, which is beneficial to ensuring the safety performance and cycle life of lithium-ion batteries.

[0006] The present application also provides a positive electrode plate, which is prepared using the mixed positive electrode material of the present application, and can improve the uniformity of distribution of the positive electrode material on the positive electrode plate, and can better meet the electrochemical performance of the lithium-ion battery.

[0007] The present application also provides a method for preparing a positive electrode plate. The preparation method of the present application adopts the mixed positive electrode material of the present application, which can improve the uniform distribution of the positive electrode material on the positive electrode plate, enhance the performance of the plate, and better meet the electrochemical performance requirements of lithium-ion batteries.

[0008] The present application also provides a secondary battery, which adopts the positive electrode plate of the present application to achieve the purpose of improving energy density while also having good electrochemical performance.

[0009] The present application also provides an electrical device, comprising the secondary battery of the present application, wherein the battery is used to provide power to the device and / or is used as an energy storage unit for the device.

[0010] The technical solution proposed in this application is:

[0011] The present application proposes a mixed positive electrode material, including a mixed component composed of a lithium iron phosphate chemical system material and a ternary chemical system material, wherein the lithium iron phosphate chemical system material is a secondary particle with a low specific surface area, and the average specific surface area does not exceed 10m 2 / g of secondary particles.

[0012] In some embodiments of the present application, the lithium iron phosphate chemical system material has an average specific surface area of ​​no more than 6m 2 / g of secondary particles.

[0013] The secondary particles of lithium iron phosphate material used in the present application should also be understood as the above-mentioned processed and agglomerated material particles. In a specific embodiment, it can refer to the secondary particles obtained by hard agglomeration of primary particles of nano-scale lithium iron phosphate chemical system.

[0014] In some embodiments of the present application, the specific surface area of ​​the secondary particles of the lithium iron phosphate chemical system is no more than 10m 2 / g. Specifically, it can be no more than 9m 2 / g, not more than 8m 2 / g, not more than 7m 2 / g. Further, it can be no more than 6m 2 / g, not more than 5m 2 / g, not more than 4m 2 / g, not more than 3m 2 In the present application, when the specific surface area of ​​the secondary particles of the lithium iron phosphate chemical system is within the above range, when mixed with the ternary chemical system material, the problems of high slurry viscosity and uneven coating on the positive electrode sheet due to agglomeration problems during the slurry making process can be avoided, thereby improving the feasibility of processing the mixed positive electrode material.

[0015] In some embodiments of the present application, the particle size distribution of the secondary particles of the lithium iron phosphate chemical system satisfies: 0.1≤D v 50 / (D v 90-D v 10)≤10. Further 0.3≤D v 50 / (D v 90-D v10)≤5, further 0.5≤D v 50 / (D v 90-D v 10)≤1. In the present application, when the particle size distribution of the secondary particles of the lithium iron phosphate chemical system is within the above range, the obtained mixed positive electrode material is more conducive to forming a more uniform mixed positive electrode slurry during the slurrying process.

[0016] In some embodiments of the present application, D v 10 and D v 90 is further limited to control the proportion of particles with smaller and larger particle sizes, so that the slurry processability of the mixed system of lithium iron phosphate chemical system secondary particles and ternary chemical system materials can be further optimized. For example, the particle size distribution of lithium iron phosphate chemical system secondary particles can meet the following requirements: v 10≥0.6μm, D v 90≤30μm; for example, D v 10≥0.8μm, D v 90≤25μm; further as D v 10≥1μm, D v 90≤20μm;D v 10≥1.2μm, D v 90≤25μm;D v 10≥2μm, D v 90≤22μm;D v 10≥3μm, D v 90≤18μm;D v 10≥4μm, D v 90≤15μm;D v 10≥5μm, D v 90≤12μm.

[0017] In some embodiments of the present application, the median particle size distribution of the secondary particles of the lithium iron phosphate chemical system satisfies: 2 μm ≤ D v 50≤9μm. For example, 3μm≤D v 50≤6μm, 2μm≤D v 50≤4μm, 4μm≤D v 50≤7μm, 5μm≤D v 50≤8μm, 6μm≤D v 50≤9μm. In the present application, when the secondary particles of the lithium iron phosphate chemical system material introduced meet the requirements of a smaller specific surface area and have a suitable median particle size distribution, it is more conducive to the uniform mixing of the secondary particles of the lithium iron phosphate chemical system and the ternary chemical system material, thereby improving the processing performance of the mixed positive electrode material.

[0018] In some embodiments of the present application, the average particle size distribution d of the primary particles constituting the secondary particles of the lithium iron phosphate chemical system satisfies: 20 nm ≤ d ≤ 800 nm. For example, d can satisfy: 300 nm ≤ d ≤ 500 nm, further 300 nm ≤ d ≤ 350 nm, 350 nm ≤ d ≤ 400 nm, 400 nm ≤ d ≤ 450 nm, 450 nm ≤ d ≤ 500 nm. In the present application, when the particle size of the primary particles constituting the LFP secondary particles is controlled within the above range, it is possible to further prevent the ternary chemical system material from deteriorating in kinetic performance and low-temperature performance due to the introduction of the LFP secondary particle material. At the same time, the hybrid system can ensure good long-term life.

[0019] In some embodiments of the present application, the powder resistivity of the secondary particles of the lithium iron phosphate chemical system is not greater than 100 Ω·cm. Specifically, it can be: not greater than 80 Ω·cm, not greater than 75 Ω·cm, not greater than 70 Ω·cm, not greater than 65 Ω·cm, not greater than 60 Ω·cm, not greater than 55 Ω·cm, 50 Ω·cm, not greater than 45 Ω·cm, not greater than 40 Ω·cm, not greater than 30 Ω·cm, not greater than 20 Ω·cm, not greater than 10 Ω·cm. In the present application, by further limiting the powder resistivity of the secondary particles of the lithium iron phosphate chemical system, the resistance of the positive electrode sheet can be effectively regulated, which is beneficial to ensuring the cycle performance of the lithium-ion battery.

[0020] In some embodiments of the present application, based on the mass of the mixed components being 100%, the mass percentage of the secondary particles of the lithium iron phosphate chemical system is controlled to be 20% - 70%. Specifically, the mass percentage of the secondary particles of the lithium iron phosphate chemical system can be 20% - 25%, 25% - 35%, 35% - 45%, 45% - 55%, 55% - 65%, 65% - 70%. In the present application, by adjusting the content of the secondary particles of the lithium iron phosphate chemical system in the mixed positive electrode material within the above range, the energy density and safety of the battery can be further optimized.

[0021] In some embodiments of the present application, the lithium iron phosphate chemical system material can adopt a lithium-containing compound with the general formula LiFe 1-x M x PO4, where 0 < x ≤ 0.1, and M can be selected from one or more of Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, or Ti.

[0022] In some embodiments of the present application, the ternary chemical system material can be a lithium nickel cobalt manganese oxide chemical system material and / or a lithium nickel cobalt aluminate chemical system material. For example, the general formula of the lithium nickel cobalt manganese oxide chemical system material can be LiNi x Mn y Co 1-x-yO2, where 1>x>0, 1>y>0, x+y≤0.95; the general formula of the nickel cobalt aluminum oxide chemical system material can be LiNi x Co y Al 1-x-y O2, where 1>x>0.6, 0.4>y>0.1.

[0023] The hybrid positive electrode material described in this application solves the agglomeration problem when the ternary chemical system material and the lithium iron phosphate chemical system material are blended by controlling the specific surface area of ​​the secondary particles of the lithium iron phosphate chemical system, improves the processing performance of the hybrid positive electrode material, realizes that the slurry is not easy to agglomerate, and improves the good compatibility between different materials. The slurry stability is enhanced, the maximum storage time of the slurry is increased, and the filterability is improved. When the hybrid positive electrode material of this application is used to prepare the positive electrode sheet, the mixed components can be evenly distributed on the positive electrode sheet, which is conducive to adjusting the uniformity of the sheet resistance distribution, thereby improving the electrochemical performance of the battery.

[0024] In a second aspect, the present application proposes a positive electrode plate, comprising a positive electrode material layer containing the above-mentioned mixed positive electrode material.

[0025] In some embodiments of the present application, the mass per unit area of ​​the positive electrode material layer is 150-250 g / m 2 Specifically, the lower limit of the mass per unit area of ​​the positive electrode material layer may be: not less than 150 g / m 2 , not less than 160g / m 2 , not less than 170g / m 2 , not less than 180g / m 2 , not less than 190g / m 2 , not less than 200g / m 2 , not less than 210g / m 2 , not less than 220g / m 2 , not less than 230g / m 2 , not less than 240g / m 2 The upper limit of the unit area mass of the positive electrode material layer can be: not more than 160g / m 2 , not more than 170g / m 2 , not more than 180g / m 2 , not more than 190g / m 2 , not more than 200g / m 2 , not more than 220g / m 2 , not more than 210g / m 2 , not more than 230g / m 2 , not more than 240g / m 2 , not more than 250g / m 2 .

[0026] In some embodiments of the present application, the compaction density of the positive electrode material layer is 2.6-3.5 g / cm 3 Specifically, the lower limit of the compaction density of the positive electrode material layer may be 2.6 g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 , 3g / cm 3 , 3.1g / cm 3 , 3.2g / cm 3 , 3.3g / cm 3 , 3.4g / cm 3 The upper limit of the compaction density of the positive electrode material layer can be 2.7 g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 , 3g / cm 3 , 3.1g / cm 3 , 3.2g / cm 3 , 3.3g / cm 3 , 3.4g / cm 3 , 3.5g / cm 3 .

[0027] In the present application, by further adjusting the mass per unit area and the compaction density of the positive electrode material layer, the resistivity of the positive electrode sheet and the capacity per unit area of ​​the positive electrode sheet can be adjusted, thereby ensuring that the prepared battery has higher dynamic performance and higher energy density.

[0028] In some embodiments of the present application, the positive electrode plate also contains a conductive agent and a binder. The conductive agent and the binder are both conventional materials in the art. For example, the conductive agent can be selected from at least one of carbon black, graphene, carbon nanotubes, Ketjen black, and carbon fiber, and the binder can be selected from at least one of polytetrafluoroethylene, polystyrene butadiene rubber, and sodium carboxymethyl cellulose. In a specific embodiment of the present application, the mass ratio of the mixed positive electrode material, the conductive agent, and the binder is about (90-98): (1-5): (1-5). For example, 96.5:1.5:2, 92:2:3, 93:3:2, 97:5:1, 98:1:5, 95:3.5:4.

[0029] The positive electrode plate of the present application, due to the use of the above-mentioned mixed positive electrode material, can achieve uniform distribution of the mixed positive electrode material on the positive electrode plate, which is beneficial to improving the uniformity of the plate resistance and can better meet the electrochemical performance of the lithium-ion battery.

[0030] On the third aspect, the present application proposes a method for preparing a positive electrode sheet, comprising the following steps: mixing the mixed positive electrode materials, filtering and collecting the slurry, coating the slurry on a current collector, removing the solvent, and then rolling and slicing to obtain a positive electrode sheet.

[0031] The preparation method of the present application adopts the mixed positive electrode material of the present application, which is beneficial to make the mixed positive electrode material more evenly distributed on the positive electrode plate, which is beneficial to improving the performance of the positive electrode plate and better meeting the electrochemical performance requirements of lithium-ion batteries.

[0032] In a fourth aspect, the present application proposes a secondary battery, comprising the above-mentioned positive electrode plate.

[0033] The positive electrode sheet of the present application is conducive to improving the uniformity of the electrode sheet resistance due to the uniform distribution of the mixed positive electrode material on the positive electrode sheet, so that the prepared battery has higher energy density and better cycle performance. The secondary battery of the present application has high energy density and good electrochemical performance.

[0034] In a fifth aspect, the present application proposes an electrical device, comprising the above-mentioned battery, wherein the battery is used to provide power to the electrical device and / or is an energy storage unit for the electrical device, and the electrical device is selected from one or more of electric vehicles, electric ships, electric tools, electronic equipment and energy storage systems.

[0035] In a specific embodiment of the present application, the electrical device may be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0036] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is a SEM image of the positive electrode sheet of Example 1;

[0038] Figure 2 This is the SEM image of the positive electrode sheet made of traditional single crystal 523 ternary material;

[0039] Figure 3a and 3b These are SEM images of positive electrode sheets prepared from secondary particles of LFP material in one embodiment of the present application at different magnifications;

[0040] Figure 4 for Figure 3a Schematic diagram of the long diameter statistics of the primary particles in the middle part;

[0041] Figure 5 The charge and discharge curve diagram of the lithium ion battery of Example 1;

[0042] Figure 6 The lithium ion battery cycle capacity retention rate curve diagram of Example 1;

[0043] Figure 7 is a schematic diagram of a lithium-ion battery of Example 1;

[0044] Figure 8 is a schematic diagram of one embodiment of a device in which a lithium-ion battery is used as a power source. DETAILED DESCRIPTION

[0045] At present, some studies have used lithium iron phosphate system materials mixed with ternary system materials as positive electrode materials to improve the safety performance and cycle life of ternary system batteries. Since the structural stability of lithium iron phosphate itself is better than that of ternary materials, it has become an industry consensus that the structural stability of the battery material system can be improved by adding a small amount of lithium iron phosphate to the ternary positive electrode material. However, as two types of materials with great differences in structure and properties, if they are not screened and mixed properly, the performance and quality of the battery may be unstable due to the high defective rate of the positive electrode, and the positive electrode material system and the overall performance of the battery may be damaged. There may be many factors affecting the defective rate. For example, the poor compatibility of the two materials leads to poor stability of the mixed slurry used to prepare the pole piece, which is easy to agglomerate, resulting in uneven distribution of the positive electrode material in the active material layer of the pole piece, thereby deteriorating the electrochemical performance of the battery.

[0046] In the first aspect, the present application proposes a mixed positive electrode material, including a mixed component composed of a lithium iron phosphate chemical system material and a ternary chemical system material, wherein the lithium iron phosphate chemical system material is a secondary particle with a low specific surface area, and the average specific surface area does not exceed 10m 2 In some embodiments, the lithium iron phosphate chemical system material has an average specific surface area of ​​no more than 6m 2 / g of secondary particles.

[0047] When the particles are very fine, they have a large specific surface area. The larger the specific surface area, the greater the surface energy. Small particles with large surface energy are easily combined together due to weak interaction forces such as van der Waals forces and hydrogen bonds, and agglomeration occurs, that is, many small particles are recombined to form larger secondary particles, that is, small primary particles are agglomerated in some way, which can be called secondary particles. As is well known, the agglomeration mode of particles can be divided into soft agglomeration or hard agglomeration. In general, the agglomeration caused by physical bonding (such as van der Waals forces, hydrogen bonds and other intermolecular forces, etc.) is soft agglomeration, and the agglomeration caused by chemical bonding is hard agglomeration. Soft agglomerations can be opened using mechanical force, but hard agglomerations are difficult to open. Therefore, the product form that can usually be called secondary particles should refer to the product obtained by processing primary particles by some artificial means to make them agglomerate. As one of the components of the positive electrode active material, the hybrid positive electrode material of the present application introduces a lithium iron phosphate chemical system material that mainly exists in the form of secondary particles. The secondary particles are required to be stable (not easy to be opened) by the present application, so the secondary particles of the lithium iron phosphate material used in the present application should also be understood as the above-mentioned processed and agglomerated material particles. In a specific embodiment, it can refer to the secondary particles obtained by hard agglomeration of the primary particles of the nano-scale lithium iron phosphate chemical system.

[0048] In the present application, the lithium iron phosphate chemical system material in the mixed positive electrode material mainly exists in the form of secondary particles, and a small amount of primary particles are inevitably doped in the mixed components, which are all within the protection scope of the present application.

[0049] In this field, the chemical system of positive electrode materials is divided according to the type of active substances, and there is no limitation on the auxiliary materials doped or added thereto. For example, materials whose active substances are lithium iron phosphate (including those doped with elements) can be defined as lithium iron phosphate chemical system materials, and materials whose active substances are represented by nickel cobalt manganese oxide system (generally referred to as NCM) and nickel cobalt aluminum oxide system (generally referred to as NCA) are defined as ternary chemical material systems.

[0050] Generally, the specific surface area of ​​lithium iron phosphate chemical system particles and ternary chemical system particles is significantly different, and they are easy to agglomerate when mixed. The inventors have found through a large number of experimental studies that the use of lithium iron phosphate chemical system secondary particles with a smaller average specific surface area, specifically, no more than 9m 2 / g, not more than 8m 2 / g, not more than 7m 2 / g. Further, it can be no more than 6m 2 / g, not more than 5m 2 / g, not more than 4m 2 / g, not more than 3m 2 / g. When the secondary particles of the lithium iron phosphate chemical system with a specific surface area are mixed with the ternary chemical system materials, the problems of high viscosity of the slurry and uneven coating on the positive electrode sheet caused by agglomeration problems during the slurry making process can be avoided, thereby improving the feasibility of processing the mixed positive electrode material.

[0051] In this application, D v X is defined as follows: Arrange the particles in ascending order of volume and label them as 1, 2, 3…n…, where the sum of the volumes of the nth particle and all particles whose volumes are less than or equal to the nth particle accounts for X% of the total volume of all particles, then the particle size of the nth particle is recorded as D v X.

[0052] D v 50 is the particle size value of the nth particle when the sum of the volumes of the first n particles accounts for 50% of the total volume. In this application, D v 50 represents the median particle size distribution. v 10 refers to the particle size value of the nth particle when the sum of the volumes of the first n particles accounts for 10% of the total volume. v 90 refers to the particle size value of the nth particle corresponding to when the sum of the volumes of the first n particles accounts for 90% of the total volume.

[0053] In this application, the narrower the particle size distribution of the secondary particles, the larger the particle size distribution. v 90 The smaller the D v The larger the value of 10, the more favorable it is for the secondary particles to adapt to the ternary chemical system materials. For example, when the particle size distribution of the secondary particles satisfies: 0.1≤D v 50 / (D v 90-D v 10)≤10, further 0.3≤D v 50 / (D v 90-D v 10)≤5, further 0.5≤D v 50 / (D v 90-D v When 10)≤1, the obtained mixed positive electrode material is more conducive to forming a more uniform mixed positive electrode slurry during the slurry making process.

[0054] When D v 10 After one hour, small particles may agglomerate. v When 90 is too large, it may clog the filter element of the lithium-ion battery slurry production equipment, and cannot form a good filling and matching with the ternary material particles with smaller particle size. In the specific embodiment of the present application, D v 10 and D v90 is further limited to control the proportion of particles with smaller and larger particle sizes, so that the mixed system of secondary particles of lithium iron phosphate chemical system and ternary chemical system materials can be further optimized. For example, the particle size distribution of secondary particles can meet the following requirements: v 10≥0.6μm, D v 90≤30μm, such as D v 10≥0.8μm, D v 90≤25μm, further as D v 10≥1μm, D v 90≤20μm;D v 10≥1.2μm, D v 90≤25μm;D v 10≥2μm, D v 90≤22μm;D v 10≥3μm, D v 90≤18μm;D v 10≥4μm, D v 90≤15μm;D v 10≥5μm, D v 90≤12μm.

[0055] The cathode material of the present application, when the secondary particles of the lithium iron phosphate chemical system material introduced have a suitable median particle size distribution while satisfying a smaller specific surface area, is more conducive to the uniform mixing of the secondary particles of the lithium iron phosphate chemical system and the ternary chemical system material, thereby improving the processing performance of the mixed cathode material. In some embodiments of the present application, the median particle size distribution of the secondary particles satisfies: 2μm≤D v 50≤9μm, for example, 3μm≤D v 50≤6μm, 2μm≤D v 50≤4μm, 4μm≤D v 50≤7μm, 5μm≤D v 50≤8μm, 6μm≤D v 50≤9μm.

[0056] By controlling the particle size of the primary particles that make up the LFP secondary particles, the electrochemical performance of the lithium-ion battery prepared by the mixed positive electrode material of the present application can be further improved. When the average particle size of the primary particles is too small, the storage performance and cycle life of the mixed system are poor. When the average particle size of the primary particles is too large, the low temperature performance and rate discharge performance of the mixed system are poor. In a specific embodiment of the present application, the average particle size distribution d of the primary particles that make up the secondary particles satisfies: 20nm≤d≤800nm. For example, when d is controlled to satisfy: 300nm≤d≤500nm, further 300nm≤d≤350nm, 350nm≤d≤400nm, 400nm≤d≤450nm, 450nm≤d≤500nm, so that the ternary chemical system material will not be due to the introduction of the LFP secondary particle material. The deterioration of the kinetic performance and low temperature performance, at the same time, the mixed system can ensure a good long-term life.

[0057] Those skilled in the art will understand that the powder resistivity of the LFP secondary particles will indirectly affect the resistance of the positive electrode sheet. Therefore, the properties of the secondary particles of the lithium iron phosphate chemical system can be further limited by the powder resistivity, for example, the powder resistivity of the secondary particles of the lithium iron phosphate chemical system is controlled to be no more than 100Ω·cm. Specifically, it can be: no more than 80Ω·cm, no more than 75Ω·cm, no more than 70Ω·cm, no more than 65Ω·cm, no more than 60Ω·cm, no more than 55Ω·cm, 50Ω·cm, no more than 45Ω·cm, no more than 40Ω·cm, no more than 30Ω·cm, no more than 20Ω·cm, no more than 10Ω·cm. In the present application, when the powder resistivity of the secondary particles of the lithium iron phosphate chemical system varies within the above range, the resistance of the positive electrode sheet can be effectively regulated, thereby facilitating the cycle performance of the lithium-ion battery.

[0058] In the present application, the battery performance can be further optimized by adjusting the content of secondary particles of the lithium iron phosphate chemical system in the mixed positive electrode material. Specifically, based on the mass of the mixed components as 100%, the mass percentage of the secondary particles of the lithium iron phosphate chemical system is controlled to be 20%-70%. For example, 20%-25%, 25%-35%, 35%-45%, 45%-55%, 55%-65%, 65%-70%. In the present application, by adjusting the content of secondary particles of the lithium iron phosphate chemical system in the mixed positive electrode material within the above range, the energy density and safety performance of the battery can be further guaranteed.

[0059] In this application, the choice of chemical system materials is not limited. For example, the general formula of LiFe 1-x M xThe lithium iron phosphate chemical system material of PO4, where 0 < x ≤ 0.1, and M can be selected from one or more of Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, or Ti.

[0060] In this application, the ternary chemical system material can be a lithium nickel cobalt manganese oxide chemical system material and / or a lithium nickel cobalt aluminum oxide chemical system material. For example, the general formula of the lithium nickel cobalt manganese oxide chemical system material can be LiNi x Mn y Co 1-x-y O2, where 1 > x > 0, 1 > y > 0, and x + y ≤ 0.95; the general formula of the lithium nickel cobalt aluminum oxide chemical system material can be LiNi x Co y Al 1-x-y O2, where 1 > x > 0.6 and 0.4 > y > 0.1.

[0061] As is well known to those skilled in the art, during the preparation process of lithium iron phosphate chemical system particles, carbon coating of the particles is further implemented to improve the conductivity of the cathode material. The lithium iron phosphate chemical system material in this application can be such that at least partial regions of the surfaces of at least some of the particles are formed with carbon coating. For example, for the preparation method of carbon-coated lithium iron phosphate, reference can be made to patent application CN101453030A. Using a compound reaction system containing a lithium source, a phosphorus source, and a carbon source, by controlling the thermodynamic and kinetic factors during the reaction process, carbon-coated lithium iron phosphate particles are obtained. It can be understood that the thickness and uniformity of the carbon coating also affect the conductivity. When the carbon coating thickness on the surfaces of all particles is basically uniform, its conductivity is the best.

[0062] In the specific implementation manner of this application, the preparation method of the lithium iron phosphate chemical system secondary particles is as follows:

[0063] (1) Using a ball mill, uniformly mix the lithium source, iron source, phosphorus source compound, optional dopant, and carbon source, and then perform low-temperature pre-sintering under a protective gas to obtain a pre-sintered material. Among them, the phosphorus source and iron source can be selected from one or a combination of two of iron phosphate or iron phosphate dihydrate, and the lithium source is one or several of lithium phosphate, lithium carbonate, and lithium nitrate; the carbon source is selected from 1 or a combination of at least 2 of ascorbic acid, cellulose, polypropylene, epoxy resin, sucrose, glucose, fructose, citric acid, polyethylene glycol, starch, and phenolic resin. The above materials are all conventional raw materials in the art, and their addition ratios only need to be able to achieve this application.

[0064] (2) Mix the above pre-sintered material with a dispersant and a solvent (deionized water or methanol), and perform ultra-fine grinding with a sand mill to obtain lithium iron phosphate chemical system primary particles. In the specific implementation manner, a small amount of carbon source can also be added during ultra-fine grinding to further improve the conductivity of the subsequent sintered product and enhance the coating at the same time.

[0065] (3) The ultrafinely ground primary particles of the lithium iron phosphate chemical system are spray dried to form monodisperse microspheres after evaporation of the solvent, and then the microspheres are sintered under a nitrogen protective atmosphere for further reaction (the reaction temperature is slightly higher than the pre-sintering temperature) to obtain secondary particles of the lithium iron phosphate chemical system. The surface of the lithium iron phosphate secondary particles can also be further carbon-coated by further vapor deposition to improve the conductivity of the material.

[0066] The hybrid positive electrode material of the present application solves the agglomeration problem when the ternary chemical system material and the lithium iron phosphate chemical system material are blended by controlling the specific surface area of ​​the secondary particles of the lithium iron phosphate chemical system, improves the processing performance of the hybrid positive electrode material, realizes that the slurry is not easy to agglomerate, and the two materials are well compatible. The slurry stability is enhanced, the maximum storage time of the slurry is increased, and the filterability is improved. When the hybrid positive electrode material of the present application is used to prepare the positive electrode sheet, the positive electrode material can be effectively controlled to be evenly distributed on the positive electrode sheet, which is conducive to adjusting the distribution uniformity of the sheet resistance.

[0067] In a second aspect, the present application proposes a positive electrode plate, comprising a positive electrode material layer containing the above-mentioned mixed positive electrode material.

[0068] In the present application, the resistivity of the positive electrode sheet can be further adjusted by controlling the mass of the positive electrode material per unit area and the compaction density of the positive electrode material. In some embodiments of the present application, the mass per unit area of ​​the positive electrode material layer is 150-250 g / m 2 Specifically, the lower limit of the mass per unit area of ​​the positive electrode material layer may be: not less than 150 g / m 2 , not less than 160g / m 2 , not less than 170g / m 2 , not less than 180g / m 2 , not less than 190g / m 2 , not less than 200g / m 2 , not less than 210g / m 2 , not less than 220g / m 2 , not less than 230g / m 2 , not less than 240g / m 2 The upper limit of the unit area mass of the positive electrode material layer can be: not more than 160g / m 2 , not more than 170g / m 2 , not more than 180g / m 2 , not more than 190g / m 2 , not more than 200g / m 2 , not more than 220g / m 2 , not more than 210g / m 2, not more than 230g / m 2 , not more than 240g / m 2 , not more than 250g / m 2 .

[0069] In some embodiments of the present application, the compaction density of the positive electrode material layer is 2.6-3.5 g / cm 3 Specifically, the lower limit of the compaction density of the positive electrode material layer may be 2.6 g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 , 3g / cm 3 , 3.1g / cm 3 , 3.2g / cm 3 , 3.3g / cm 3 , 3.4g / cm 3 The upper limit of the compaction density of the positive electrode material layer can be 2.7 g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 , 3g / cm 3 , 3.1g / cm 3 , 3.2g / cm 3 , 3.3g / cm 3 , 3.4g / cm 3 , 3.5g / cm 3 .

[0070] In the present application, by further adjusting the mass per unit area and the compaction density of the positive electrode material layer, the resistivity of the positive electrode sheet and the capacity per unit area of ​​the positive electrode sheet can be adjusted, thereby ensuring that the prepared battery has higher dynamic performance and higher energy density.

[0071] In some embodiments of the present application, the positive electrode plate also contains a conductive agent and a binder. Both the conductive agent and the binder are conventional materials in the art. For example, the conductive agent can be selected from at least one of carbon black, graphene, carbon nanotubes, Ketjen black, and carbon fiber, and the binder can be selected from at least one of polytetrafluoroethylene, polystyrene-butadiene rubber, and sodium carboxymethyl cellulose. In a specific embodiment of the present application, the mass ratio of the mixed component, the conductive agent, and the binder is about (90-98): (1-5): (1-5), for example, 96.5: 1.5: 2, 92: 2: 3, 93: 3: 2, 97: 5: 1, 98: 1: 5, 95: 3.5: 4.

[0072] The positive electrode sheet of the present application is beneficial to improving the distribution uniformity of the positive electrode sheet resistance because the mixed positive electrode material is well distributed on the positive electrode sheet, and can better meet the electrochemical performance of the lithium-ion battery.

[0073] On the third aspect, the present application proposes a method for preparing a positive electrode sheet, comprising the following steps: mixing the mixed positive electrode materials, filtering and collecting the slurry, coating the slurry on a current collector, removing the solvent, and then rolling and slicing to obtain a positive electrode sheet.

[0074] The preparation method of the present application adopts the mixed positive electrode material of the present application, which is beneficial to improve the uniformity of distribution of the positive electrode material on the positive electrode sheet, improve the resistance uniformity of the positive electrode sheet, and better meet the electrochemical performance requirements of lithium-ion batteries.

[0075] In a fourth aspect, the present application proposes a secondary battery, comprising the above-mentioned positive electrode plate.

[0076] The positive electrode plate of the present application is good and evenly distributed on the positive electrode plate, which is beneficial to improving the distribution uniformity of the plate resistance, so that the prepared battery has higher energy density and better cycle performance.

[0077] The battery of the present application has high energy density and also has good electrochemical performance.

[0078] In a fifth aspect, the present application proposes an electrical device, comprising the above-mentioned battery, the battery being used to provide power to the electrical device and / or being an energy storage unit for the electrical device, and the electrical device is selected from one or more of electric vehicles, electric ships, electric tools, electronic equipment and energy storage systems.

[0079] In a specific embodiment of the present application, the electrical device may be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0080] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application.

[0081] The embodiments of the present application are described in detail below. The embodiments are exemplary and intended to be used to explain the present application, but should not be construed as limiting the present application.

[0082] In the following examples and comparative examples, the following tests were performed:

[0083] 1. Secondary particle specific surface area test

[0084] Reference standard: GB / T 19587-2004 "Determination of specific surface area of ​​solid substances by gas adsorption BET method"

[0085] As an example, the specific process is as follows:

[0086] (1) Take a certain amount of sample: if it is lithium iron phosphate secondary particles, 2.0-4g is required; if it is ternary material, 8.0-15.0g is required;

[0087] (2) Place the sample in a sample tube, place it in a heating pack, and degas (degassing conditions: 200°C, 2 hours);

[0088] (3) After degassing is completed, when the temperature of the degassing station drops to room temperature, remove the sample tube from the degassing station and weigh and calculate the total mass of the sample;

[0089] (4) Place the sample tube into the test filling rod and perform the BET test.

[0090] 2. Secondary particle size distribution test

[0091] Reference standard: GB / T 19077.1-2016

[0092] As an example, the specific process is as follows:

[0093] (1) Take a clean beaker and add the sample to be tested (the sample concentration should ensure that the shading degree is 8%-12%);

[0094] (2) Add about 20 g of alcohol solution and perform external ultrasound for 5 min to ensure that the sample is completely dispersed;

[0095] (3) Turn on the sample injection system, then turn on the optical system, preheat for 30 minutes, and then conduct the test;

[0096] (4) After inputting the corresponding parameters, the instrument automatically measures and obtains the results.

[0097] 3. SEM image acquisition

[0098] Take the cold-pressed electrode, cut it open perpendicular to its large surface using an Ar particle beam to expose the end face, and obtain a picture using a scanning electron microscope.

[0099] 4. Primary particle size test

[0100] The particle size is counted using the long diameter statistical method: Figure 3a and Figure 4 As shown, Figure 4 The length of the line segment indicated in Figure 3a The length of the primary particles in the long diameter direction is measured according to the size shown in the SEM image. Figure 4The diameters of the three groups of primary particles in the long axis direction are measured, with at least 10 particles in each group measured. The average value of the three groups is taken to obtain the particle size of the primary particles.

[0101] 5. Powder resistivity test

[0102] Reference standard: GB / T 30835-2014 "Carbon composite lithium iron phosphate positive electrode materials for lithium-ion batteries"

[0103] Test method: Place a certain mass of mixed cathode material sample in the feeding cup of the resistivity tester, then compact the sample, collect data manually, and record the powder resistivity test results at different pressure points.

[0104] As an example, the specific process is as follows:

[0105] (1) Sample weighing: Weigh a certain weight of sample, and the sample weight should be controlled between 0.8-2.4g;

[0106] (2) Adding: Add the weighed sample into the adding cup, making sure that all the weighed sample is added into the adding cup;

[0107] (3) Pressurization: Compact the sample and ensure that the compaction pressure is 8 MPa;

[0108] (4) Data collection: When the pressure is 8 MPa, collect powder resistivity data.

[0109] 6. Slurry viscosity test method

[0110] Reference standard: GB / T 10247-2008 Viscosity measurement method, test temperature 25°C

[0111] Test instrument: Accuracy: ±1% FS, Brookfield DV2T viscometer;

[0112] Principle description: When the rotor (cylinder) rotates continuously in the fluid, the viscous torque of the fluid acts on the rotor (cylinder). At a certain speed, the dynamic viscosity of the fluid is proportional to the torque.

[0113] 7. Slurry solid content test method

[0114] Weigh a certain amount of lithium-ion battery slurry, dry it at 120-125°C until the mass is constant, and the mass fraction of the sample mass after drying to the original sample mass is taken as the solid content of the slurry.

[0115] As an example, the specific process is as follows:

[0116] (1) Take a well-stirred slurry sample (3.0±0.2 g) and place it in a weighing bottle that has been dried and weighed (accurate to 0.0002 g), quickly cover it, weigh it (accurate to 0.0002 g), and shake it to level it;

[0117] (2) Open the bottle cap and place the weighing bottle and bottle cap in a drying oven that has been pre-aired and heated to 120-125°C. Dry under air-blowing conditions for 1 hour.

[0118] (3) Take out the weighing bottle from the drying oven, cover it immediately, cool it in air for about 3 minutes, put it in a desiccator, cool it to room temperature, and weigh it;

[0119] (4) Calculation of results: Solid content = (total weight of solid matter after drying / total weight of slurry before drying).

[0120] Test methods 1-7 are all tests performed simultaneously based on the preparation process of the positive lithium-ion battery. If the test is performed on the lithium-ion battery that has been prepared, the following steps can be added:

[0121] 1) Battery disassembly

[0122] a. The battery is fully discharged to a full discharge state with a voltage of 2.0V;

[0123] b. Disassemble the battery in the glove box and control the humidity in the glove box to less than 2%;

[0124] c. Separate the positive electrode from the battery, then soak and fully wash off the electrolyte on the positive electrode with DMC (dimethyl carbonate);

[0125] d. Take out the positive electrode and place it in a vacuum drying oven and dry it at 80°C for 5 hours.

[0126] 2) Active substance separation

[0127] a. Separate the dried positive electrode active material layer and the current collector;

[0128] b. The separated active substance is ground into powder and dissolved with NMP (N-methylpyrrolidone) under heating conditions, and then filtered and the residue is collected, and the dissolution and filtration steps are repeated until the PVDF binder is fully removed;

[0129] c. Filter and dry the mixture after fully washing away the binder.

[0130] d. Conductive carbon separation

[0131] Disperse the dried mixture powder in a liquid medium (the density of the liquid medium is greater than 1.2 g / cm 3 , for example, nitrobenzene, bromobenzene, carbon tetrachloride, etc.), and stirred to make it basically uniformly mixed. After standing for a long enough time, the solution is layered, the upper layer is conductive carbon, and the lower layer is active material.

[0132] 3) Separation of lithium iron phosphate chemical system materials and ternary chemical system materials

[0133] Principle: Since the density difference between the ternary chemical system materials and the lithium iron phosphate chemical system materials is smaller than the difference between the positive electrode materials and the conductive carbon, when separating the ternary positive electrode materials and the lithium iron phosphate positive electrode materials, it is necessary to further utilize the difference in surface wetting properties between the two: the surface of the lithium iron phosphate chemical system materials is carbon-coated and hydrophobic; the surface of the ternary chemical system materials is more hydrophilic.

[0134] Specific steps:

[0135] a. Drying the active material in the lower layer to obtain a mixture powder;

[0136] b. Similar to the coal screening process, select a suitable liquid medium (such as water, ethylene glycol or propylene glycol, etc.) and a suitable flotation agent (such as fat oil 190, fusel alcohol, etc.), and use bubble flotation method for separation.

[0137] The specific steps are: take 1 kg of mixed positive electrode material in a liquid medium, adjust to a more appropriate solid content, add a flotation agent, stir to generate bubbles, collect the floating foam, wash and dry, and then you can get lithium iron phosphate chemical system materials; collect the slurry at the bottom, wash and dry, and then you can get ternary chemical system materials.

[0138] c. Dry the separated ternary chemical system materials and lithium iron phosphate chemical system materials and perform subsequent characterization analysis respectively.

[0139] 8. Test of battery capacity and battery energy density (Note: When the system is a pure lithium iron phosphate system, the charge cut-off voltage is 3.65V and the discharge cut-off voltage is 2.0V; when the system is a pure ternary chemical system or a chemical system mixed with ternary, the charge cut-off voltage is 4.35V and the discharge cut-off voltage is 2.8V)

[0140] The capacity in this application is expressed as the capacity of the battery cell measured at 25°C with a 1 / 3C constant current (wherein the charge / discharge current is the rate multiplied by the rated capacity of the battery cell, and the rated capacity is based on the battery cell capacity identified in the GBT certification document of the battery cell, the battery module to which the battery cell belongs, or the battery pack to which the battery cell belongs), and within the operating voltage range specified in the GBT certification document. The specific process of the example is as follows:

[0141] 1) Place the battery in a 25°C oven for 2 hours until the battery temperature remains at 25°C;

[0142] 2) 1 / 3C constant current discharge to discharge cut-off voltage;

[0143] 3) Pause for 5 minutes;

[0144] 4) 1 / 3C constant current charging charging cut-off voltage, continue constant voltage charging until the charging current is less than 0.05C;

[0145] 5) Pause for 5 minutes;

[0146] 6) 1 / 3C constant current discharge to the discharge cut-off voltage (this step is the actual battery test capacity. Combined with the mass of the cathode active material, the gram capacity of the positive electrode material can be calculated; the battery energy can be calculated by integrating the voltage-capacity curve, energy value / battery weight value = battery mass energy density).

[0147] 9. Battery cycle performance test

[0148] The number of cycles when the capacity decays to 80% of the initial value (Note: when the system is a pure lithium iron phosphate system, the charge cut-off voltage is 3.65V and the discharge cut-off voltage is 2.5V; when the system is a pure ternary chemical system or a chemical system mixed with ternary, the charge cut-off voltage is 4.35V and the discharge cut-off voltage is 2.8V). The specific process is as follows:

[0149] 1) 45℃, 1C / 1C cycle test process:

[0150] 2) Place the battery in a 45°C oven for 2 hours until the battery temperature remains at 45°C;

[0151] 3) 1C constant current charging to the charging cut-off voltage, and continue constant voltage charging until the charging current is less than 0.05C;

[0152] 4) Pause for 5 minutes;

[0153] 5) 1C constant current discharge to the discharge cut-off voltage;

[0154] 6) Pause for 5 minutes;

[0155] Step 2) to step 6) is a charge and discharge cycle of the battery. Figure 5 The figure shows the number of cycles when the above steps 2 to 6 are continuously cycled until the capacity decays to 80% of the initial value.

[0156] The PVDF used in the examples and comparative examples of this application was purchased from Solvay Co., Ltd., model 5130, with an average molecular weight of 800,000-1.5 million;

[0157] Sodium carboxymethyl cellulose (CMC) was purchased from Foshan Ruimeida New Materials, lithium battery series CMC;

[0158] The separator was purchased from Enjie New Materials Co., Ltd. and is a ceramic separator for lithium iron phosphate lithium-ion batteries;

[0159] The electrolyte was purchased from Guangdong Tianci New Materials Co., Ltd. and is an electrolyte for lithium iron phosphate lithium-ion batteries;

[0160] The negative electrode sheet preparation method of the present application is exemplified as follows:

[0161] Preparation of negative electrode sheet: artificial graphite, conductive carbon black, binder (styrene-butadiene rubber) and sodium carboxymethyl cellulose (CMC) are dissolved in a solvent in proportion, stirred evenly to form a slurry, and the slurry is evenly coated on the copper foil current collector. After drying, cold rolling, slitting and cutting in sequence, the negative electrode sheet is obtained.

[0162] The present application is described in detail below through specific embodiments:

[0163] Example 1

[0164] Example 1 proposes a mixed positive electrode material, a positive electrode sheet prepared therefrom, and a lithium-ion battery.

[0165] (1) Mixed positive electrode materials

[0166] The mixed positive electrode material of Example 1 includes a mixed component consisting of lithium iron phosphate chemical system secondary particles and ternary chemical system powder in a mass ratio of about 3:7. The specific composition parameters are shown in Table 1.

[0167] Among them, the molecular formula of the secondary particles of the lithium iron phosphate chemical system is: LiFe 0.98 Mn 0.02 PO4, the average specific surface area is about 10m 2 / g,D v 50 is about 5μm, D v 10 is about 1.5μm, D v 90 is about 13.5μm, and D is calculated v 50 / (D v 90-D v 10)=0.42, the particle size of the primary particles constituting the lithium iron phosphate secondary particles is about 400nm.

[0168] The molecular formula of the ternary chemical system powder is LiNi 0.5 Co 0.2 Mn .0.3 O2, with a specific surface area of ​​about 1.2m 2 / g,D v 50 is about 3μm.

[0169] The mixed positive electrode material of Example 1 also includes conductive carbon black and PVDF, wherein the mass ratio of the mixed component to the conductive carbon black and PVDF is about 96.5:1.5:2.

[0170] (2) Positive electrode sheet and preparation method thereof

[0171] The mixed positive electrode materials were mixed at a speed of about 500 r / min, and then N-methylpyrrolidone (NMP) was added and stirred at a speed of about 2000 r / min. Then, the mixture was filtered with a filter screen of about 200 mesh to obtain a slurry with a viscosity of about 8000 mPa·S, and the solid content in the slurry was measured. The mixture was coated on an aluminum foil with a thickness of about 13 μm, and then NMP was evaporated and removed. The mixture was rolled and sliced ​​to obtain a compacted density of about 3.1 g / cm 3 , coating weight is about 190g / m 2 The SEM results of the positive electrode are shown in Figure 1 .

[0172] Figure 2 This is a cross-sectional SEM image of a positive electrode sheet made from traditional single crystal 523 ternary positive electrode material. Although the ternary material particles are evenly distributed, there are many unfilled spaces between the particles. Figure 3a and Figure 3b The SEM images of the positive electrode sheet of the secondary particles of the LFP material at different magnifications show that, although the secondary particles are evenly distributed, there are also many unfilled spaces between the particles. At the same time, there are a large number of nano-grain boundaries inside the secondary particles, and the secondary particles have a dense structure.

[0173] like Figure 1 As shown in the figure, the LFP secondary particles and ternary materials in the mixed positive electrode material are evenly and densely distributed without agglomeration. In addition, it can be seen that there are obvious nanocrystalline boundaries inside the LFP secondary particles.

[0174] (3) Lithium-ion battery and its preparation method

[0175] The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence, and then wound to obtain a bare cell, which is then packaged, injected, and formed to obtain a lithium-ion battery. Figure 7 As shown, the energy density and cycle performance were measured. The results are shown in Table 3. Figure 5 and Figure 6 .

[0176] Figure 5 The curve diagram illustrating three charge and discharge cycles of the lithium-ion battery of Example 1 is obtained by continuously cycling the same lithium-ion battery three times under the same test conditions. It can be seen that the three charge and discharge cycles are not much different, the three curves are almost overlapped, and there is almost no capacity decay.

[0177] Figure 6The attenuation of the cycle capacity retention rate of the lithium-ion battery of Example 1 is shown. The two curves record the attenuation of the cycle capacity retention rate of the two lithium-ion batteries respectively. The attenuation of the two tests is almost the same, without much difference. It can be seen from the trend of the curve that the capacity of the lithium-ion battery prepared in Example 1 has an upward trend in the first few cycles. This is mainly because as the cycle progresses, the internal material is continuously activated and the electrolyte is fully infiltrated, resulting in the battery activation factor being greater than the attenuation factor, thereby improving the capacity. As the cycle continues, the capacity attenuation factor increases and is greater than the activation factor, causing the battery capacity to continue to decay, but the decay is slow. Until the 225th cycle, the capacity retention rate is still close to 98%. From Figure 6 It can be seen that the lithium ion battery of Example 1 has very good cycle performance.

[0178] Example 2-25

[0179] Examples 2-25 According to the specific components and proportions shown in Table 1, the positive electrode sheet and lithium-ion battery were prepared using the method shown in Example 1.

[0180] Embodiment 26

[0181] like Figure 8 As shown, embodiment 26 provides a device, which is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the device's requirements for high power and high energy density of lithium-ion batteries, a battery pack or battery module prepared from the above lithium-ion batteries can be used.

[0182] Embodiment 27

[0183] Embodiment 27 provides a mobile device, which may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be light and thin, and uses the above-mentioned lithium-ion battery as a power source.

[0184] Comparative Example 1

[0185] Comparative Example 1 proposes a mixed positive electrode material, a positive electrode sheet prepared therefrom, and a lithium-ion battery.

[0186] The difference between Comparative Example 1 and Example 2 is that the LiFe 0.98 Mn 0.02 The average specific surface area of ​​PO4 secondary particles is about 12m 2 / g, composition LiFe 0.98 Mn 0.02 The primary particle size of PO4 secondary particles is about 10 nm, and the other steps and parameters are the same.

[0187] Comparative Example 2

[0188] Comparative Example 2 proposes a mixed positive electrode material, a positive electrode sheet prepared therefrom, and a lithium-ion battery.

[0189] The difference between Comparative Example 2 and Example 2 is that the LiFe 0.98 Mn 0.02 The average specific surface area of ​​PO4 secondary particles is about 17m 2 / g, the other steps and parameters are the same.

[0190] Comparative Example 3

[0191] Comparative Example 3 proposes a mixed positive electrode material, a positive electrode sheet prepared therefrom, and a lithium-ion battery.

[0192] The difference between Comparative Example 3 and Example 2 is that the mixed positive electrode material of Comparative Example 3 includes primary particles of lithium iron phosphate chemical system and powder of ternary chemical system in a mass ratio of about 3:7, LiFe 0.98 Mn 0.02 The specific surface area of ​​PO4 primary particles is about 16m 2 / g,D v 50 is about 1.1μm, D v 10 is about 0.25 μm, D v 90 is about 18.5 μm, and the other steps and parameters are the same.

[0193] The specific parameters of the mixed components of Examples 1-25 and Comparative Examples 1-3 are shown in Table 1.

[0194] Table 1

[0195]

[0196]

[0197] The solid content of the mixed slurries of Examples 1-6 and Comparative Examples 1-3 was measured, and the battery energy density and cycle performance were measured. The results are shown in Table 2.

[0198] Table 2

[0199] Solid content of mixed slurry (%) Battery energy density (Wh / kg) Cycling performance (45℃80% EOL) Example 1 64.0 225 1260 Example 2 65.5 228 1390 Example 3 66.0 230 1480 Example 4 67.5 235 1350 Example 5 68.0 220 1200 Example 6 70.0 215 1100 Comparative Example 1 55.0 185 800 Comparative Example 2 53.0 165 600 Comparative Example 3 46.0 160 350

[0200] The positive electrode sheet resistance of Examples 1-25 and Comparative Examples 1-3, as well as the energy density and cycle performance of lithium-ion batteries including the positive electrode sheets were measured. The results are shown in Table 3.

[0201] Table 3

[0202]

[0203]

[0204] In the preparation process of Comparative Example 1-3, the slurry could not pass through the 150-mesh steel wire screen continuously and stably, and the agglomerated slurry was blocked on one side of the filter screen, and the filtration could not be completed. In addition, the viscosity of the slurry before and after mixing was tested and it was found that after the slurry was mixed, the viscosity increased significantly and the fluidity deteriorated significantly, indicating that a more serious agglomeration phenomenon occurred. In the preparation process of Example 1-25, the mixed slurry could pass through the 150-mesh steel wire screen continuously and stably without clogging, indicating that no agglomeration phenomenon occurred. At the same time, the viscosity of the slurry was measured, and it was found that the viscosity of the mixed slurry did not change much compared with that before mixing.

[0205] Comparing the solid content of the mixed slurry of Example 1-6 with that of Comparative Example 1-3, it can be seen that the specific surface area of ​​the secondary particles in Example 1-6 is not greater than 10m 2 / g, the solid content of the final mixed slurry is much greater than that of Comparative Examples 1-3. The reason is mainly because the mixed positive electrode materials of Examples 1-6 did not agglomerate during the preparation process, and still had good slurry stability and processing performance at a higher solid content. The mixed positive electrode materials of Comparative Examples 1-3 will agglomerate during the preparation process. When the solid content increases, the agglomeration phenomenon becomes more serious, so the solid content of the mixed positive electrode material finally prepared will also decrease. Low-solid content slurry is prone to diaphragm cracking and uneven coating thickness control during the coating process, thereby affecting the battery energy density and cycle performance. In particular, as shown in Comparative Example 3, comparing Table 2 and Table 3 at the same time, when the mixed material uses nano-scale lithium iron phosphate primary particles, the solid content of the mixed slurry is only 46%, which is much less than the solid content of the mixed slurry of Examples 1-6, which seriously affects the energy density and cycle performance of the battery.

[0206] Comparing Table 3, it can be seen from Examples 1-6 and Comparative Examples 1-2 that the energy density of the lithium battery finally prepared by using the average value of the specific surface area of ​​LFP in the embodiments of the present application is improved, and finally, when the initial discharge capacity and the first cycle efficiency are basically the same, the number of cycles when the capacity decays to 80% of the initial value is significantly increased, which is much greater than the number of cycles in the comparative example, and the cycle performance of the lithium battery is significantly improved.

[0207] Comparing Examples 7-9 and 12-14 with Examples 10, 11, 15, and 16, it can be seen that D v 50. D v 10. D v 90 and D v 50 / (D v 90-D v 10) has an impact on the resistivity and cycle life of the electrode sheet. The mixed positive electrode materials of Examples 7-9 and 12-14 of the present application, D v 50. D v 10. D v90 and D v 50 / (D v 90-D v The value of 10) is guaranteed to be within an appropriate range, and the resistance of the positive electrode sheet finally prepared is low. When the initial discharge capacity and the first cycle efficiency are basically the same, the number of cycles when the capacity decays to 80% of the initial value increases significantly, indicating that the appropriate secondary particle size distribution has a great influence on the battery performance.

[0208] Comparing Examples 17-21 and Examples 22-24, it can be seen that the proportion of mixed positive electrode materials has a great influence on the resistance of the positive electrode sheet, the energy density and cycle performance of the lithium battery. From Examples 17-21, it can be seen that with the increase in the mass fraction of lithium iron phosphate secondary particles, the resistance of the positive electrode sheet decreases, the battery energy density decreases slightly, and the cycle performance increases. From Examples 22-24, it can be seen that excessive addition of ternary materials may affect the battery energy cycle performance, and the improvement of energy density is limited.

[0209] In summary, the hybrid positive electrode material of the present application solves the agglomeration problem when the ternary chemical system material and the lithium iron phosphate chemical system material are blended by controlling the specific surface area of ​​the secondary particles of the lithium iron phosphate chemical system, improves the processing performance of the hybrid positive electrode material, realizes that the slurry is not easy to agglomerate, and the two materials are well compatible. When the hybrid positive electrode material of the present application is used to prepare the positive electrode sheet, the positive electrode material can be evenly distributed on the positive electrode sheet, which is conducive to adjusting the distribution uniformity of the electrode sheet resistance value, so that the prepared lithium ion battery has a higher energy density and better cycle performance.

[0210] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0211] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A secondary battery, characterized in that: The mixed positive electrode material includes a mixed component composed of a lithium iron phosphate chemical system material and a ternary chemical system material, and the lithium iron phosphate chemical system material has an average specific surface area of ​​3m 2 / g~10m 2 / g of secondary particles.

2. The secondary battery according to claim 1, characterized in that: The lithium iron phosphate chemical system material has an average specific surface area of ​​3.5 m 2 / g~7m 2 / g of secondary particles; Optionally, the lithium iron phosphate chemical system material has an average specific surface area of ​​4m 2 / g~6m 2 / g of secondary particles.

3. The secondary battery according to claim 1 or 2, characterized in that: The particle size distribution of the secondary particles satisfies: 0.03≤D v 50 / (D v 90-D v 10)≤10; Optionally, 0.07≤D v 50 / (D v 90-D v 10)≤10; Optionally, 0.1≤D v 50 / (D v 90-D v 10)≤10; Optionally, 0.21≤D v 50 / (D v 90-D v 10)≤5; Optionally, 0.37≤D v 50 / (D v 90-D v 10)≤5; Optionally, 0.42 ≤ D v 50 / (D v 90-D v 10)≤5; Optionally, 0.5≤D v 50 / (D v 90-D v 10)≤1; Optionally, 0.63 ≤ D v 50 / (D v 90-D v 10)≤1.

4. The secondary battery according to any one of claims 1 to 3, characterized in that: The particle size distribution of the secondary particles satisfies: D v 10≥0.1μm, D v 90≤41.5μm; Optionally, D v 10≥0.2μm, D v 90≤33.5μm; Optionally, D v 10≥0.6μm, D v 90≤30μm; Optionally, D v 10≥0.8μm, D v 90≤25μm; Optionally, D v 10≥1μm, D v 90≤20μm; Optionally, D v 10≥1.2μm, D v 90≤25μm; Optionally, D v 10≥1.5μm, D v 90≤41.5μm; Optionally, D v 10≥2μm, D v 90≤22μm; Optionally, D v 10≥3μm, D v 90≤18μm; Optionally, D v 10≥4μm, D v 90≤15μm; Optionally, D v 10≥5μm, D v 90≤12μm.

5. The secondary battery according to any one of claims 1 to 4, characterized in that: The median particle size distribution of the secondary particles satisfies: 2μm≤D v 50≤20μm; Optionally, 2μm≤D v 50≤10μm; Optionally, 2μm≤D v 50≤9μm.

6. The hybrid secondary battery according to claim 5, characterized in that: The median particle size distribution of the secondary particles satisfies: 3 μm ≤ D v 50≤6μm.

7. The secondary battery according to any one of claims 1 to 6, characterized in that: The average particle size distribution d of the primary particles constituting the secondary particles satisfies: 20nm≤d≤800nm; Optionally, 300nm≤d≤500nm; Optionally, 300nm≤d≤350nm; Optionally, 350nm≤d≤400nm; Optionally, 400nm≤d≤450nm; Optionally, 450nm≤d≤500nm.

8. The secondary battery according to any one of claims 1 to 7, characterized in that: The powder resistivity of the secondary particles of the lithium iron phosphate chemical system is not greater than 100 Ω·cm.

9. The secondary battery according to any one of claims 1 to 8, characterized in that: Based on the mass of the mixed components being 100%, the content of the secondary particles of the lithium iron phosphate chemical system is 20%-70%; Optionally, the content of secondary particles of the lithium iron phosphate chemical system is 20%-25%; Optionally, the content of secondary particles of the lithium iron phosphate chemical system is 45%-55%; Optionally, the content of secondary particles of the lithium iron phosphate chemical system is 55%-65%; Optionally, the content of secondary particles in the lithium iron phosphate chemical system is 65%-70%.

10. The secondary battery according to claim 9, characterized in that: The content of secondary particles in the lithium iron phosphate chemical system is 25%-45%; Optionally, the content of secondary particles of the lithium iron phosphate chemical system is 25%-35%; Optionally, the content of secondary particles in the lithium iron phosphate chemical system is 35%-45%.

11. The secondary battery according to any one of claims 1 to 10, characterized in that: In the mixed components: The general formula of the lithium iron phosphate chemical system material is LiFe 1-x M x PO4, where 0 < x ≤ 0.1, and M is selected from one or more of Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, and Ti; and / or The ternary chemical system material is a nickel cobalt manganese oxide lithium chemical system material and / or a nickel cobalt aluminum oxide lithium chemical system material. The general formula of the nickel cobalt manganese oxide lithium chemical system material is LiNi x Mn y Co 1-x-y O2, wherein 1>x>0, 1>y>0, x+y≤0.95; the general formula of the nickel cobalt aluminum oxide chemical system material is LiNi x Co y Al 1-x-y O2, where 1>x>0.6, 0.4>y>0.

1.

12. The secondary battery according to any one of claims 1 to 11, characterized in that: The positive electrode sheet comprises a positive electrode material layer containing the mixed positive electrode material, and the unit area mass of the positive electrode material layer is 150-250g / m 2 , and / or The compaction density of the positive electrode material layer is 2.6-3.5 g / cm 3 .

13. The secondary battery according to claim 12, characterized in that: The positive electrode material layer also contains a conductive agent and a binder, and the mass ratio of the mixed positive electrode material, the conductive agent and the binder is (90-98):(1-5):(1-5).

14. The secondary battery according to claim 12 or 13, characterized in that: The method for preparing the positive electrode sheet comprises the following steps: The mixed positive electrode material is mixed, Filter and collect the slurry, The slurry is coated on a current collector, After removing the solvent, rolling and slicing are performed. Get the positive electrode.

15. The secondary battery according to claim 14, characterized in that: The solid content of the slurry is 60% to 70%.

16. An electrical device, characterized in that: The secondary battery comprises the secondary battery according to any one of claims 1 to 15, wherein the secondary battery is used to provide power for the electrical device and / or is an energy storage unit for the electrical device, and the electrical device is selected from one or more of electric vehicles, electric ships, electric tools, electronic equipment and energy storage systems.

Citation Information

Patent Citations

  • Fastening method for integrated fuel cell pack

    CN101453030A

Cited By

  • Positive electrode material, positive electrode plate, battery and electric device

    CN121054653A